2011
DOI: 10.1530/joe-11-0096
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 4-methylbenzylidene camphor, daidzein, and estrogen on intact and osteotomized bone in osteopenic rats

Abstract: The study investigated the influence of 4-methylbenzylidene camphor (4-MBC), daidzein, and estradiol-17b-benzoate (E 2 ) on either intact or osteotomized cancellous bone in ovariectomized (Ovx) rats. Three-month old Ovx rats were fed with soy-free (SF) diet over 8 weeks; thereafter, bilateral transverse metaphyseal osteotomy of tibia was performed and rats were divided into groups: rats fed with SF diet and SF diet supplemented with 4-MBC (200 mg), daidzein (50 mg), or E 2 (0 . 4 mg) per kilogram body weight. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…One of the potential reasons for these inconsistencies could be due to the individual differences in the flavonoids metabolism. Recently, it has been suggested that the clinical effectiveness of flavonoids might partly depend on the ability to produce equol, a gut bacterial metabolite of daidzein showing stronger estrogenic activity than the predominant flavonoids [32, 33]. …”
Section: Resultsmentioning
confidence: 99%
“…One of the potential reasons for these inconsistencies could be due to the individual differences in the flavonoids metabolism. Recently, it has been suggested that the clinical effectiveness of flavonoids might partly depend on the ability to produce equol, a gut bacterial metabolite of daidzein showing stronger estrogenic activity than the predominant flavonoids [32, 33]. …”
Section: Resultsmentioning
confidence: 99%
“…For histological analyses, the entire tibia was embedded in methyl methacrylate (Merck, Darmstadt, Germany) and cut longitudinally at a thickness of 150 μm using diamond saw microtome (Leica SP 1600, Leica Biosystems GmbH, Nussloch, Germany) (Komrakova et al, 2011a, Komrakova et al, 2011b). Three central representative sections were microradiographed with the aid of faxitron Cabinet X-ray system (Hewlett-Packard, Buffalo Grove, IL, USA) using Kodak 100 NIF Industrex Film (SR45, Kodak) and mounted on glass slides with a medium (Eukitt, O Kindler GmbH, Freiburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…) and potential protective role for osteoporosis and menopausal symptoms (Komrakova et al . ). After ingestion, dietary isoflavones are subjected to degradation by specific isoflavone biotransforming bacteria in the gut.…”
Section: Introductionmentioning
confidence: 97%